Focus on Science, Technology, Society and Environment (CTSA) on the themes of Science Fair projects (Research, Society and Development, 2021)
Science fairs are extremely important spaces for the dissemination of scientific culture. They are shown as a fundamental tool in the development of both students and teachers, as those involved are encouraged to seek the necessary methodologies to achieve continuous knowledge in all areas. This study seeks to carry out a documental analysis on the themes addressed in Science Fairs promoted by a university in the interior of RS, considering the Science, Technology, Society and Environment (CTSA) approach. This is a study with a qualitative, exploratory and descriptive nature, with documental analysis being carried out. Data analysis was similar to Content Analysis. Two categories of analysis were obtained: “Importance of children and adolescents in studies aimed at CTSA” and “Themes addressed in research projects”. It was observed that the presentations on Science and Society were the chosen theme for most of the works. The thematic choices of students somehow refer to their concern with our society and their use of available resources, demonstrating critical awareness, evident in their concern with the development of society.